Attention Deficit and Hyperactivity Symptoms in Children with Convergence Insufficiency: Based on of Teacher and Parent Reports - Rezaee, Masoome; Dibajnia, Parvin (Journal of Clinical Physiotherapy Research, 2023)
Introduction: This research intends to determine the occurrence of ADHD-related symptoms in children with Convergence Insufficiency (CI), a treatable visual issue that may be misconstrued as ADHD. It focuses on understanding how often these behaviors are noticed by parents and educators in various environments, such as home and school. Methods: This was a case–control study and 108 children attended. Eye examinations were performed and the children were divided into the with CI and control groups. The Children Symptoms Inventory-4 (CSI-4) questionnaire was completed by teachers and parents. CSI-4 is a rating scale that screens for emotional and behavioral symptoms of childhood disorders. These questionnaires ask the parent and teachers to rate the frequency of behaviors observed: never, sometimes, fairly often, or most of the time. Results: A total of 108 school-aged children were evaluated by parents and 100 of them by the teachers. There were 51% girls in the CI group and 49% in the control group. Comparison of the mean scores of the parent questionnaire in CI group and control group in ADHD symptoms showed that these two groups did not have significant difference (P<0.05) in ADHD symptoms. The results of the teacher questionnaire indicated that these two groups had a significant difference (P<0.05) for inattention symptom. Conclusion: The results from this study suggested that based on teacher information, CI children have a higher frequency of inattentive behaviors, compared to normal binocular children. ADHD may make diagnosis of CI difficult, exacerbate the symptoms of CI and vice versa. For children who have ADHD symptoms or other learning difficulties, a comprehensive visual examination can be useful for diagnosis of CI and other vision problems.